Pengaruh Kelelahan Kerja, Kepuasan Kerja, dan Work Life Balance terhadap Kinerja Karyawan Perusahaan Alat Tulis - Dendy Novandi; Cletrisovi Cletrisovi; Nawfa Kayla Kautsarani; Nia Nahdiyah Septiani (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of work fatigue, job satisfaction, and work-life balance on employee performance at PT Zebra Asaba Industries. An associative quantitative approach was used, with data collected through closed questionnaires distributed to Millennial and Gen Z employees. The data were analyzed using multiple linear regression with the help of SPSS software. The results show that job satisfaction has a significant effect on employee performance, while work fatigue and work-life balance do not show a significant effect, either partially or simultaneously. These findings suggest that increasing job satisfaction is key to improving employee productivity. Although fatigue and work-life balance were not significant in this study, they still warrant attention as they may affect long-term performance. The study recommends that management focus on enhancing job satisfaction through improvements in work environment, compensation, and interpersonal relationships. Future research is advised to explore other potential factors such as motivation, organizational culture, or leadership style that may have a greater impact on performance.